Case reports of amniotic membrane derived-cell treatment for feline chronic renal failure - Seul Ah Noh; Taeho Kim; Junguk Ju (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Three different cats who had chronic kidney disease (CKD) were treated for more than one month with fluid therapy in an animal clinic. Although this long-term treatment and hospitalization, there was no clinical improvement in clinical signs as well as serum biochemical indexes including blood urea nitrogen (BUN), creatinine (CREA), and phosphate (PHOS). All cases were then injected three times with allogeneic stem cells through an intravenous route for treatment on Day 0, 7, and 14 or 30. On the same day, clinical observation and blood tests for serum biochemistry were conducted together. Upon administrating stem cells to the CKD cats, clinical conditions and the indexes of BUN and CREA were clinically improved within normal ranges. Additionally, one of the cats who had the renal cysts presented clinical improvement with showing decreased cysts size than before.